University-SME clusters: A research on commercialization perspective among IPTA & IPTS in Malaysia - A. P., Puvanasvaran (Penerbit UTeM, 2012)
The purpose of this study was to expose the scope and dimension of university research commercialization Malaysia. The study conducted under a fundamental framework base on the university commercialization perspective, which consist of IPTA (government benefactor universities) and IPTS (private benefactor universities).The study discuss on the practicality of commercialization practices among universities, what are the barriers facing by the university towards commercialization and what are the research commercialization achievement in recent years. The study focuses on the university and SMEs or small meduim enterprises clusters in achieving commercialization in recent years among IPTA and IPTS University in Malaysia. The study contributes a fundamental framework of commercialization perspective in university of Malaysia, which has deferent application and withdraws valuable information towards in assisting the university organization as well higher education ministry in planning, positioning and mounting strategies in the effort of achieving highest level of university research commercialization.